Globotriaosylsphingosine (Lyso‐Gb3) as a biomarker for cardiac variant (N215S) Fabry disease. Issue 2 (2nd January 2018) - Alharbi, Fahad J.; Baig, Shanat; Auray‐Blais, Christiane; Boutin, Michel; Ward, Douglas G.; Wheeldon, Nigel; Steed, Rick; Dawson, Charlotte; Hughes, Derralynn; Geberhiwot, Tarekegn
Abstract: Fabry disease (FD) is a multi‐systemic X‐linked lysosomal disorder caused by the deficient activity of α‐galactosidase‐A enzyme, which leads to accumulation of glycosphingolipids in various body tissues. The N215S mutation is a known variant of FD, with a late onset cardiac phenotype. Consensus guidelines acknowledged the use of globotriaosylsphingosine (Lyso‐Gb3 ) as a diagnostic marker for classical FD but its utility for cardiac variant FD is not clear. We aim to characterize the clinical features and evaluate the diagnostic accuracy of plasma and urinary Lyso‐Gb3 levels in N215S cardiac variant FD patients. Thirty‐four FD patients with the late‐onset N215S cardiac variant mutation were enrolled along with 62 classical FD patients and 109 healthy controls. Plasma and urinary Lyso‐Gb3 and its analogues were analyzed by LC‐MS/MS. Both FD males and females with N215S mutation showed Lyso‐Gb3 levels of (mean ± SEM) 9.7 ± 1.0 and 5.4 ± 0.8 nM, respectively. These levels were significantly higher than healthy control and lower than classical FD patients ( p  < 0.0001). Plasma Lyso‐Gb3 levels equal to or higher than 2.7 nM yielded a diagnostic sensitivity and specificity of 100% (AUC = 1, p < 0.0001). Cardiac involvement was frequent with 16/34 (47%) developing left ventricular hypertrophy. Three patients who underwent renal biopsy had the characteristic sphingolipid deposition in the podocytes while 6/19 (32%) had evidence of white matter changes or infarct on brain MRI. Taken together, cardiac variant N215S mutation is rather an attenuated form of classical FD. Plasma Lyso‐Gb3 is a diagnostic hallmark to differentiate N215S variant phenotype from subjects with no FD.